Trophic State of the Bandar Kayangan Lembah Sari Reservoir Based on Trophic Index (TRIX), Rumbai Pesisir District, Pekanbaru - Bennawaty Bennawaty; Asmika Harnalin Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThere are several human activities such as floating cages, tourism and daily activities are conducted around the Bandar Kayangan Lembah Sari Reservoir and thus the remains of pollutant may enter to the water and affects the trophic state in the reservoir. Trophic Index (TRIX) can be used to determine the trophic state of waters based on chemical and biological parameters. To understand the trophic state of the Bandar Kayangan Lembah Sari Reservoir’s waters based on Vollenweider’s Trophic Index (TRIX), a research has been conducted in March - April 2018. There were four sampling stations, namely station 1 (in the riverine zone of the Ambang River), station 2 (in the riverine zone of the Merbau River), station 3 (in the transition of the reservoir) and station 4 (in the lacustrine of the reservoir). In each station there were three sampling points, in the surface, in the middle of water column, and in the base of water. Sampling were conducted 3 times, once/week. Water quality parameters measured were DIN, total phosphorus, dissolved oxygen, chlorophyll-a, transparency, temperature and pH. Results shown that the transparency was 65.17 - 74.33 cm, temperature 27.33 - 29.33 0C, pH 5, total phosphorus 0.20 - 0.54 mg/L, DIN 0.09 - 0.18 mg/L, chlorophyll-a13.76 - 19.56µg/L, oxygen saturation 62.37 - 100.48%. Trophic Index (TRIX) value of the Bandar Kayangan Lembah Sari Reservoir was 3.79 - 6.45, and it indicates that the Bandar Kayangan water is in mesotrophic to hypereutrophic. Keywords : Ambang River, Merbau River, Water Quality, Vollenweider’sTrophic Index